(untitled) (Contemporary Journal of Social Science Review, 2024)
The present study aimed to investigate the analysis of students’ perceived English test anxiety at the Secondary Level, with a specific focus on examining the gender-based differences. This quantitative research utilized a survey as the primary data collection method and focused on the population of all government schools in the Multan district. From this extensive population, a sample of 513 male students and 392 female students was selected, totaling 905 participants, to gather pertinent data. To ensure the validity and reliability of the research instrument, a pre-existing questionnaire was employed for data collection. Statistical analysis, including descriptive statistics, t-tests, and ANOVA, were employed to ascertain differences and relationships between various variables within the study. The research findings unveiled a significant disparity in the opinions of male and female students regarding the perception of English test anxiety. These findings have practical implications for improving English education and ensuring that all Secondary-level students can thrive in their learning experiences.